Fibroblast growth factor signaling in macrophage polarization: impact on health and diseases - Shen, Luyao; Li, Yongsheng; Zhao, Huakan (Frontiers in Immunology, 2024)
Fibroblast growth factors (FGFs) are a versatile family of peptide growth factors that are involved in various biological functions, including cell growth and differentiation, embryonic development, angiogenesis, and metabolism. Abnormal FGF/FGF receptor (FGFR) signaling has been implicated in the pathogenesis of multiple diseases such as cancer, metabolic diseases, and inflammatory diseases. It is worth noting that macrophage polarization, which involves distinct functional phenotypes, plays a crucial role in tissue repair, homeostasis maintenance, and immune responses. Recent evidence suggests that FGF/FGFR signaling closely participates in the polarization of macrophages, indicating that they could be potential targets for therapeutic manipulation of diseases associated with dysfunctional macrophages. In this article, we provide an overview of the structure, function, and downstream regulatory pathways of FGFs, as well as crosstalk between FGF signaling and macrophage polarization. Additionally, we summarize the potential application of harnessing FGF signaling to modulate macrophage polarization.